2006
DOI: 10.1177/0022487105285591
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Linguistic Diversity from the Outset

Abstract: Schools of education typically prepare their prospective teachers to work with amorphous “average students”—who are by implication middle class, native, English speaking, and White. They are then given some limited opportunities to adapt these understandings to students with diverging profiles—children of poverty, second language learners, and students of color. The authors argue that given the changing demographics of public schools, initial teacher education should be based on the understandings that teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Big ideas about language include knowledge of linguistics (Ann & Peng, 2005;Valdés et al, 2005), linguistic diversity (Valdés et al, 2005), social justice issues (Bartolomé & Balderrama, 2001), linguistically responsive practices (Lucas et al, 2008), and EL instructional strategies (Commins & Miramontes, 2006).…”
Section: Collaborative Teacher Learning For Cultural and Linguistic Dmentioning
confidence: 99%
“…Big ideas about language include knowledge of linguistics (Ann & Peng, 2005;Valdés et al, 2005), linguistic diversity (Valdés et al, 2005), social justice issues (Bartolomé & Balderrama, 2001), linguistically responsive practices (Lucas et al, 2008), and EL instructional strategies (Commins & Miramontes, 2006).…”
Section: Collaborative Teacher Learning For Cultural and Linguistic Dmentioning
confidence: 99%
“…Several scholars have addressed teachers' understanding of how to work with linguistically diverse children (Arias & Poynor, 2001;Commins & Miramontes, 2006;de la Piedra, 2007). Arias and Poynor (2001), for example, called for the infusion of cultural and linguistic traditions of students into the curriculum as an enactment of valuing and respecting the diversity of the students.…”
Section: Supporting Els In Mathematics Classroomsmentioning
confidence: 99%
“…Making connections between the students' cultures and the curriculum by valuing what students bring with them from home is of great importance. In addition, research has indicated different strategies available to empower ELs with mathematics such as organizing instruction in a way that is meaningful, promoting challenging activities and higher order thinking, planning instructional activities to account for language proficiency, and promoting dialogue to engage students in the learning process (Commins & Miramontes, 2006;Minaya-Rowe & Ortiz, 2010). Some of these strategies include demonstrations, illustrations, and real experiences working in small groups collaboratively, and participating in authentic communication (Haynes, 2010;Lessow-Hurley, 2013).…”
Section: Supporting Els In Mathematics Classroomsmentioning
confidence: 99%
“…In addition, teachers may be uncomfortable talking about how diversity affects learning contexts or recognizing its significance within classroom interactions (FlorioRuane, 2001). Race, culture, poverty, special needs, and social justice need to be addressed in ways that help teachers recognize their perspectives and engage in meaningful experiences to develop and expand their knowledge of multicultural education (Commins & Miramontes, 2006;Cooper, 2007). There is still a great deal to be known about what makes teachers effective as they work with students in multicultural settings and most of the studies have focused on preservice teacher education (Cochran-Smith, 2004;Knight and Wiseman. Multicultural education has been defined as a framework for considering classroom interactions and designing learning contexts that make educational opportunities equitable for diverse groups in our society.…”
Section: Theoretical Framework and Related Researchmentioning
confidence: 99%